IMPLEMENTASI SISTEM PELAYANAN MITRA PADA PT. PELINDO II (PERSERO) CABANG TANJUNG PRIOK JAKARTA - Redaksi Tim Jurnal (PETIR, 2017)
Pelabuhan Indonesia II or PELINDO II Tanjung Priok Branch is a State-Owned Enterprises engaged in port service activities. The service of ships and goods is a task carried on the environment of the port of PT. PELINDO II Tanjung Priok Branch. Information Technology is needed for service activities can be presented quicklu, presely and efficiently. PT. PELINDO II Tanjung Priok Branch has implemented Information Communication Technology (ICT) based system. However, the uster division is still using masnual methods in relation to customer complaints service to ship operational activities and good such as the many obstacles they are very disturbing the operational activities and complaints are known still onlu limited to the TOP Manager Level. And with the existence of the service system, then the company, especially employees who are facing directly in the field will know the various complaints felt by partner/ customer during the service users who are environment PT. PELINDO II Tanjung Priok Branch